FEATURES OF THE IMPLEMENTATION OF BIM TECHNOLOGIES IN THE DESIGN DEVELOPMENT PROCESS OF ARCHITECTURAL COMPANIES - Шадыбеков, Темирхон (SWorldJournal, 2021)
The paper discusses the complexities of the transition to parametric design of architectural companies associated with the features of the existing line of software. Some software products and ways of their interaction with information design technologie